PENGEMBANGAN PERMAINAN BOLA TANGAN GAWANG PANTUL UNTUK PEMBELAJARAN PENJASORKESPENGEMBANGAN PERMAINAN BOLA TANGAN GAWANG PANTUL UNTUK PEMBELAJARAN PENJASORKES - Yulita Yulita (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2016)
Abstract: This study aims to produce a model of the game of handballgoalkeeper used reflective 1) as an alternative big ball game Penjasorkes inaccordance with the characteristics of primary school children, 2) toimprove the quality of learning Penjasorkes. Development procedure usedhad some steps : 1) Product analyzing for development; 2) developing firstproduct of playing; 3) expert validating; 4) small group test; 5) productrevised; 6) big group test; 7) product revised and result product ofdevelopment. Result of the research was a bound gate handball playingproduct that could used as a penjasorkes learning model, based from bigscale test that showed : 1) for Penjasorkes teachers as responden was 1.000(a thousand). It could conclusioned reliabilitation result for Penjasorkesteachers respon, it said reliabel because “r’ calculated bigger than “r” tablewas 0,997 with signification level 5%. 2) Students responden data as lasingin assessment of taken with cognitif indicator was 76,6%; psikomotorindicator was 71,1%; afektif indicator was 87,1%. ammount increasedlearning pulse was 85,31% . The conclusion that development of bound gatehandball playing model for Penjasorkes learning at Elementary School hadbeen resulted an effective product for increased fitness body students.Key Word: development, bound gate of handball playing, big ballAbstrak: Penelitian ini bertujuan menghasilkan model permainan bolatangan gawang pantul yang digunakan 1) sebagai alternativ permainanbola besar penjasorkes yang sesuai dengan karakteristik anak sekolah dasar,2)dapat meningkatkan kualitas pembelajaran penjasorkes. Prosedurpengembangan yang digunakan meliputi beberapa tahapan: 1)menganalisiproduk yang dikembangkan, 2) mengembangkan produk awal permainan, 3)validasi ahli, 4) uji kelompok kecil, 5) revisi produk, 6) uji kelompok besar,7) revisi produk dan hasil produk pengembangan. Hasil penelitian iniberupa produk permainan bola tangan gawang pantul yang dapat digunakansebagai medel pembelajaran penjasorkes, berdasarkan uji skala besarmenunjukkan: 1) untuk guru Penjasorkes sebagai responden yaitu 1.000Dapat disimpulkan hasil reliabilitas untuk respon guru Penjasorkesdikatakan reliabel karena r hitung lebih besar dari r tabel yaitu 0,997 dengantaraf signifikan 5%. 2) Data responden siswa sebagai penguat dalampenilaian yang diambil dengan indikator kognitif sebesar 76,6%, Indikatorpsikomotor sebesar 71,1%,Indikator afektif sebesar 87,1%, 4) kenaikanjumlah denyut nadi pembelajaran 85,31%. Kesimpulan, bahwapengembangan model permainan bola tangan gawang pantul untukpembelajaran Penjasorkes di SD menghasilkan suatu produk yang efektifuntuk meningkatkan kebugaran jasmani siswa.Kata Kunci: Pengembangan, Permainan bola tangan gawang pantul, bolabesar